Population dynamics and molecular profiling of microbial ecosystems during spontaneous fermentation of Garcinia Mangostana Pericarps: article / Nik Abdul Hafiidz Nik Abdul Malek and Mohamad Sufian So'aib - Nik Abdul Malek, Nik Abdul Hafiidz; So'aib, Mohamad Sufian (2017)
The spontaneous fermentation has resultant product has inconsistent microbiological and sensory qualities. This study aims to establish the microfloral diversity of spontaneous fermentation of G. Mangostana pericarps, to determine population dynamics properties of spontaneous fermentation of Garcinia Mangostana Pericarps and to identify microorganism present at different stages of fermentation. The Garcinia Mangostana Pericarps fermentation was carried out anaerobically for 100 days at room temperature and sample collection was done on daily basis. Enumeration of microbial population was done on different selective media and pure culture was isolated. The Genomic DNA of pure culture was isolated and further PCR amplified using universal primer set. The 16S rRNA sequence analysis was done using Blastn and the phylogenetic tree was constructed. Due to indigenous microflora of spontaneous fermentation, 13 major genera was found which is Klebslella, Enterobector, Msngovibactor, Escherichia, Cronobactor, Komagataeibacter, Lactobacillus, Bacillus, Meyerozyma, Saccharomycete, Hanseniaaspora, Mycobacterium and Pichia. The predominant microorganisms present in fermented GMP were LAB (Log CFU/mL 2.723579±0.171854 to 3.74846±0.315589 ). Lactobacillus brevis and Lactobacillus plantarum were the dominant members of LAB. Lactic acid fermentation inhibit many pathogenic bacteria through the production of organic acids, mainly lactic acid, and cause rapid acidification during fermentation cause the dominant species of LAB survive toward end of fermentation. The survival study showed that these pathogens could survive up to 21 days. The diverse indigenous LAB microflora provides a prospective consortium for product development in future improving the quality and safety of fermented Garcinia Mangostana Pericarps..